Flow Pathways of Abyssal Water in the Yap Trench and Adjacent Channels and Basins - Liu, Xuehai; Liu, Yongzhi; Cao, Wei; Li, Dong (Frontiers in Marine Science, 2022)
Abyssal flow pathways in the Yap Trench and adjacent regions were investigated by computing geostrophic flows and analyzing water properties. Using boundary values of potential temperature, salinity, oxygen, and silicate, the upper and lower Circumpolar Deep Waters (UCPW, LCPW) were identified as the main abyssal water masses in the trench. At the western East Mariana Basin, some of the LCPW enters the southern Mariana Trench, and the remainder reaches the northern basin and then partly turns to the northern Mariana Trench, eventually joining the southern trench. At the Yap-Mariana Junction, some LCPW enters the West Mariana Basin, and the remainder passes the region east of the Yap Trench and then flows or subsides to the northern and southern trenches, respectively. In the northern trench, the LCPW flows north into the West Mariana Basin. The UCPW enters the northern Yap Trench via the East Mariana Basin and the Mariana Trench, reaches the sill of the Yap Trench via the East Caroline Basin and a narrow channel, and enters the southern trench via the East/West Caroline and Philippine Basins. The UCPW and LCPW circulate anticlockwise in the southern trench and in the northern region of it, respectively. The LCPW may be driven by the downwelling in the trench.